Postattenuation neurologic signs after surgical correction of congenital portosystemic shunts in cats: A narrative review. Issue 3 (11th January 2023) - Mullins, Ronan A.; Serrano Creheut, Tomas
Abstract: Development of postattenuation neurological signs (PANS) is a potentially severe complication after surgical attenuation of congenital portosystemic shunts in cats. This review summarizes findings of 15 publications that report occurrence of PANS in cats. PANS includes seizures but also milder neurologic signs such as blindness, ataxia, abnormal behavior, tremors, and twitching. Incidence of PANS and specifically postattenuation seizures in studies including a minimum of five cats ranges from 14.3% to 62.0% and 0% to 32.0%, respectively. Etiology of PANS in cats is unknown, however, several hypotheses have been proposed including central nervous system disease/derangement, perioperative hypoglycemia and electrolyte disturbances, and postoperative portal hypertension. A number of possible risk factors have been identified including lower grades of intraoperative postocclusion mesenteric portovenography and osmolality at 24 h postoperatively. Evidence for use of prophylactic antiepileptics such as levetiracetam to prevent or reduce incidence of PANS in cats is limited and does not support their use. Because the cause is unknown, treatment is aimed at controlling neurologic signs, preventing progression to more severe signs, and providing general supportive care. Prospective studies comparing the efficacy of different antiepileptics for treatment of PANS in cats are required. Prognosis for recovery is variable and dependent on severity of neurologic signs. For cats surviving to discharge, long‐term survival is possible but persistence or recurrence of neurologic signs in the long‐term is not uncommon.